2016
DOI: 10.1038/srep27471
|View full text |Cite
|
Sign up to set email alerts
|

Thyrostimulin-TSHR signaling promotes the proliferation of NIH:OVCAR-3 ovarian cancer cells via trans-regulation of the EGFR pathway

Abstract: Gonadotropin signaling plays an indispensable role in ovarian cancer progression. We previously have demonstrated that thyrostimulin and thyroid-stimulating hormone receptor (TSHR), the most ancient glycoprotein hormone and receptor pair that evolved much earlier than the gonadotropin systems, co-exist in the ovary. However, whether thyrostimulin-driven TSHR activation contributes to ovarian cancer progression in a similar way to gonadotropin receptors has never been explored. In this study, we first found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(64 reference statements)
4
15
0
1
Order By: Relevance
“…Consistent with functional characterization in vitro, the overexpression of NBAT-1 leads to signifcantly metastasis-related factors (MMP-2 and MMP-9) downregulated both in OVCAR-3 and TOV112D cell lines compared to the empty vector group (Figure 4A and B). As reported previously, the ERK1/2 and AKT signal pathways are usually activated in OC 14,15. As in previously published articles, our study showed that p-ERK1/2 and p-AKT protein expressions were reduced in the pcDNA-NBAT-1 group compared to the empty vector group in both TOV112D and OVCAR-3 cell lines.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with functional characterization in vitro, the overexpression of NBAT-1 leads to signifcantly metastasis-related factors (MMP-2 and MMP-9) downregulated both in OVCAR-3 and TOV112D cell lines compared to the empty vector group (Figure 4A and B). As reported previously, the ERK1/2 and AKT signal pathways are usually activated in OC 14,15. As in previously published articles, our study showed that p-ERK1/2 and p-AKT protein expressions were reduced in the pcDNA-NBAT-1 group compared to the empty vector group in both TOV112D and OVCAR-3 cell lines.…”
Section: Resultssupporting
confidence: 89%
“…However, recent evidence suggests that TSHR is highly expressed in ovarian cancer tumors (60). Patients with high tumor TSHR expression levels had lower survival rates compared to patients with low TSHR tumor expression levels (61).…”
Section: Thyroid-stimulating Hormone Receptormentioning
confidence: 99%
“…Th e human ovarian carcinoma cell line NIH:OVCAR-3 expresses both GPA2 and GPB5 suggesting that these cells also express thyrostimulin (Huang et al 2016). NIH:OVCAR-3 expresses functional TSHR, which is also present in mammalian OSE (Sun et al 2010).…”
Section: Th E Functional Role Of Thyrostimulinmentioning
confidence: 99%
“…Th is is noteworthy as EGFR is linked with the progression of ovarian cancer (Glaysher et al 2013). Moreover, an EGFR inhibitor partially inhibits thyrostimulin-induced ERK phosphorylation and completely inhibits thyrostimulininduced AKT activation (Huang et al 2016). Both of these pathways regulate epithelial ovarian cancer proliferation, further highlighting the potential role of thyrostimulin in the progression of ovarian cancer (Chan et al 2012;Cheaib et al 2015).…”
Section: Th E Functional Role Of Thyrostimulinmentioning
confidence: 99%
See 1 more Smart Citation